Comparison of intraoperative radiotherapy as a boost vs. simultaneously integrated boosts after breast-conserving therapy for breast cancer - Stoian, Raluca; Exner, Jan-Philipp Harald; Gainey, Mark; Erbes, Thalia; Gkika, Eleni; Popp, Ilinca; Spohn, Simon K. B.; Krug, David; Juhasz-Böss, Ingolf; Grosu, Anca-Ligia; Sprave, Tanja (Frontiers in Oncology, 2023)
Background Currently, there are no data from randomized trials on the use of intraoperative radiotherapy (IORT) as a tumor bed boost in women at high risk of local recurrence. The aim of this retrospective analysis was to compare the toxicity and oncological outcome of IORT or simultaneous integrated boost (SIB) with conventional external beam radiotherapy (WBI) after breast conserving surgery (BCS). Methods Between 2009 and 2019, patients were treated with a single dose of 20 Gy IORT with 50 kV photons, followed by WBI 50 Gy in 25 or 40.05 in 15 fractions or WBI 50 Gy with SIB up to 58.80–61.60 Gy in 25–28 fractions. Toxicity was compared after propensity score matching. Overall survival (OS) and progression-free survival (PFS) were calculated using the Kaplan–Meier method. Results A 1:1 propensity-score matching resulted in an IORT + WBI and SIB + WBI cohort of 60 patients, respectively. The median follow-up for IORT + WBI was 43.5 vs. 32 months in the SIB + WBI cohort. Most women had a pT1c tumor: IORT group 33 (55%) vs. 31 (51.7%) SIB group (p = 0.972). The luminal-B immunophenotype was most frequently diagnosed in the IORT group 43 (71.6%) vs. 35 (58.3%) in the SIB group (p = 0.283). The most reported acute adverse event in both groups was radiodermatitis. In the IORT cohort, radiodermatitis was grade 1: 23 (38.3%), grade 2: 26 (43.3%), and grade 3: 6 (10%) vs. SIB cohort grade 1: 3 (5.1%), grade 2: 21 (35%), and grade 3: 7 (11.6%) without a meaningful difference (p = 0.309). Fatigue occurred more frequently in the IORT group (grade 1: 21.7% vs. 6.7%; p = 0.041). In addition, intramammary lymphedema grade 1 occurred significantly more often in the IORT group (11.7% vs. 1.7%; p = 0.026). Both groups showed comparable late toxicity. The 3- and 5-year local control (LC) rates were each 98% in the SIB group vs. 98% and 93% in the IORT group (LS: log rank p = 0.717). Conclusion Tumor bed boost using IORT and SIB techniques after BCS shows excellent local control and comparable late toxicity, while IORT application exhibits a moderate increase in acute toxicity. These data should be validated by the expected publication of the prospective randomized TARGIT-B study.